Translation of Encephalomyocarditis Viral RNA in Oocytes of Xenopus laevis - Laskey, R. A. (1972)
RNA from encephalomyocarditis virus was injected into oocytes of Xenopus laevis. After incubation of the oocytes in [(35)S]methionine, polyacrylamide gel electrophoresis showed that a new series of polypeptides had been synthesized. They were identical in size to the polypeptides that appeared in ascites cells after infection with this virus. Electrophoretic and chromatographic analysis of the methionine-containing tryptic peptides from three of the induced polypeptides confirmed that they were virus-specific. All of the bands that appeared in ascites cells after infection also appeared in oocytes after injection of RNA from the virus. We conclude that Xenopus oocytes translate a mammalian viral mRNA faithfully and extensively, and perform normal post-translational modifications.